USTIFICATION OF THE SELECTION OF COLLEGES FOR THE ORGANIZATION OF RESEARCH ON THE DEVELOPMENT OF THE ENTREPRENEURIAL COMPETENCE OF FUTURE ARTISTS-PERFORMERS (Innovative professional education, 2023)
The number of professional colleges that prepare future performing artists with the specialization «Fine Art» and derivatives («Painting», «Art design») has been determined. The substantiation of the volume of sampling frame for the pedagogical experiment on the development of entrepreneurial competence in future performing artists is presented to ensure the representativeness of its results.
Keywords: professional education, sampling frame, entrepreneurial competence, youth entrepreneurship, performing artists